Research on measurement method for high-frequency pulsation flow of hydrogen circulating pump. (5th May 2023) - Zhai, Huanle; Li, Wei; Ji, Leilei; Li, Shuo; Cao, Yonghua; Li, Yongkang
Abstract: The hydrogen circulating pump (HCP) used for hydrogen recovery and utilization, affects the performance of the hydrogen fuel cell system. In this paper, aiming at the measurement research blank of the output pressure and flow high-frequency pulsation curve of the HCP, a pressure-based flow measurement method and an overlapping grid-based simulation calculation method are proposed and then compared in multiple directions for mutual verification. The research results show that the waveform errors of the pressure pulsation curves are under 2.4%, and that of the flow pulsation curves are 6.2% and 8.3%, comparing the experimental data and simulation data when the average outlet pressure is 9 kpa and 27 kpa respectively. Further study of the internal fluid characteristics, the pressure and the density change the same and produce the lowest value before the meshing point, the leakage flow rate at the rotor-rotor gap is greater than that at the rotor-pump casing gap, and the vortices show cyclical change of co-evolution and co-growth in the low-pressure area and the high-pressure area. The research results can optimize the structural design of the HCP itself, and can also refine the input conditions of the fuel cell system and contribute to performance improvement. Highlights: An indirect method for measuring real-time flow is proposed. Overlapping grid simulation method is verified reliability by experimental data. Compare and analyze the real-time flow curves of experiment and simulation. The periodic variation law of fluid parameters in the pump chamber is revealed.